Dosimetric Evaluation of The Tomotherapy, Non-coplanar and Coplanar IMRT Plannings for Total Scalp Irradiation - Songul Barlaz Us; Esil Kara; Asli Yazici; Bahar Dirican; Eda Kaya Pepele; Simay Gurocak (Medicine Science, 2015)
In this study, the dosimetric effects of the Tomotherapy, noncoplanar and coplanar IMRT plannings were evaluated for the total scalp irradiation. Tomotherapy based and linac based IMRT plans were compared for 61 years old female patient with multipl myeloma. Two different linac based IMRT plans which are coplanar and noncoplanar were performed for total scalp irradiation. 20 Gy was given to the PTV volume. Firstly, homogeneity index and conformity index values were calculated for PTV. Secondly, the doses of organ at risk (OaR) which are lenses, brain, brainstem and parotid glands were dosimetrically evaluated. While, tomotherapy plan was more homogenous, noncoplanar plan was more conformal than the others. Our study figure out that the OaR doses can be decreased by using tomotherapy based IMRT. However, the treatment time was increased when the tomotherapy based IMRT used for treatment. Tomotherapy based IMRT can be used for total scalp irradiation with respect to OaR. [Med-Science 2015; 4(2.000): 2155-64]